Electrode Type and Placement Configuration for Quadriceps Activation Evaluation - Pietrosimone, Brian G. (The National Athletic Trainers' Association, Inc., 2011)
CONTEXT: The ability to accurately estimate quadriceps voluntary activation is an important tool for assessing neuromuscular function after a variety of knee injuries. Different techniques have been used to assess quadriceps volitional activation, including various stimulating electrode types and electrode configurations, yet the optimal electrode types and configurations for depolarizing motor units in the attempt to assess muscle activation are unknown. OBJECTIVE: To determine whether stimulating electrode type and configuration affect quadriceps central activation ratio (CAR) and percentage-of-activation measurements in healthy participants. DESIGN: Crossover study. SETTING: Research laboratory. PATIENTS AND OTHER PARTICIPANTS: Twenty participants (13 men, 7 women; age = 26 ± 5.3 years, height = 173.85 ± 7.3 cm, mass = 77.37 ± 16 kg) volunteered. INTERVENTION(S): All participants performed 4 counter-balanced muscle activation tests incorporating 2 different electrode types (self-adhesive, carbon-impregnated) and 2 electrode configurations (vastus, rectus). MAIN OUTCOME MEASURE(S): Quadriceps activation was calculated with the CAR and percentage-of-activation equations, which were derived from superimposed burst and resting torque measurements. RESULTS: No differences were found between conditions for CAR and percentage-of-activation measurements, whereas resting twitch torque was higher in the rectus configuration for both self-adhesive (216 ± 66.98 Nm) and carbon-impregnated (209.1 ± 68.22 Nm) electrodes than in the vastus configuration (209.5 ± 65.5 Nm and 204 ± 62.7 Nm, respectively) for these electrode types (F(1,19) = 4.87, P = .04). In addition, resting twitch torque was greater for both electrode configurations with self-adhesive electrodes than with carbon-impregnated electrodes (F(1,19) = 9.33, P = .007). Bland-Altman plots revealed acceptable mean differences for agreement between electrode type and configuration for CAR and percentage of activation, but limits of agreement were wide. CONCLUSIONS: Although these electrode configurations and types might not necessarily be able to be used interchangeably, differences in electrode type and configuration did not seem to affect CAR and percentage-of-activation outcome measures.